Navigating the Labyrinth: A Normative Juridical Analysis of Legal Politics and Policy Formulation in Indonesia - Deden Abdul Malik; Melinda Dina Gusela; Sailan Holilul Azfa; Silvanus Fauziansah; Utang Rosidin (Enigma in Law, 2024)
This article delves into the intricate relationship between law, politics, and society in Indonesia, examining how legal politics shape the formulation of legal policies. It explores the concept of legal politics as a guiding force in Indonesian lawmaking, considering the interplay of power dynamics, social norms, and external pressures. The study employs a normative juridical method with a legislative and conceptual approach. It analyzes relevant legal documents, including legislation, regulations, and policy papers, alongside academic literature on legal and political theory. A comprehensive review of relevant legal and political theories, including legal positivism, critical legal studies, and alternative perspectives, provides the framework for analysis. The research reveals that legal politics in Indonesia function as a multifaceted instrument, serving as a mechanism for social regulation, legislative formation, and power control. The study identifies a tendency towards group dominance in the legislative process, raising concerns about justice and equitable representation. Furthermore, the influence of globalization and international pressures on national policy formulation is evident. In conclusion, legal politics play a strategic role in shaping Indonesia's legal system, influencing policy formulation, implementation, and enforcement. To foster a just and inclusive legal system, legal reform and social advocacy are crucial, particularly in addressing the complex dynamics of domestic and global politics. The findings underscore the importance of theoretical frameworks in understanding the interplay between law and politics and guiding legal reform efforts.